2005
DOI: 10.1111/j.1875-595x.2005.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranking countries by dental status using the DMFT and FS-T indices

Abstract: These findings suggest that it may be more useful to use the FS-T index with the DMFT index in studies comparing dental status between countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
0
19
0
2
Order By: Relevance
“…Among participants aged 40–49 years and 50–59 years, mean DFT increased and mean ST largely remained stable, but is likely to decrease in the future sequentially in the group aged 40–44 years, based on the trend illustrated in . Another study has reported a high DMFT index and large numbers of functional (filled or sound) teeth in 35–44‐year‐old Japanese subjects, and ranked Japanese dental health status second among those in 30 developed or developing countries 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Among participants aged 40–49 years and 50–59 years, mean DFT increased and mean ST largely remained stable, but is likely to decrease in the future sequentially in the group aged 40–44 years, based on the trend illustrated in . Another study has reported a high DMFT index and large numbers of functional (filled or sound) teeth in 35–44‐year‐old Japanese subjects, and ranked Japanese dental health status second among those in 30 developed or developing countries 3 .…”
Section: Discussionmentioning
confidence: 99%
“…These extreme interpretations of DMFT are real and occur in high‐ and low‐income countries as well as between different socio‐economic groups within the same metropolis. When the FS‐T index representing the number of functional (Filled and Sound) teeth was compared with DMFT among 35‐ to 44‐year olds on a country basis, the DMFT values were found to be higher in high‐income countries than in low‐income (156). However, the FS‐T values would indicate that the dental health status was better in high‐income countries than in low‐income countries (Table 3), where the F‐component is much lower and the D‐component much higher.…”
Section: Disease Burdens – Whose Burdens?mentioning
confidence: 99%
“…The first study reported a direct proportional relationship between per capita GDP, mean number of filled teeth and the care index in 35-to 44-year-old adults [Brunton et al, 2003]. The second study found lower dental caries levels among 35-to 44-year-old adults in developed countries than in developing countries [Namal et al, 2005]. However, there are no reports comparing the relation of caries experience and dental care levels to absolute and relative income in rich countries.…”
mentioning
confidence: 92%